1999
DOI: 10.1097/00007691-199902000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Goal-Oriented and Model-Based Clinical Pharmacokinetic Dosing of Aminoglycosides on Clinical Outcome: A Cost-Effectiveness Analysis

Abstract: The benefits of a pharmacy-based, active therapeutic drug monitoring (TDM) service (ATM) on outcomes were examined in a prospective study at four hospitals. ATM involved pharmacokinetic dosage optimization at the start of treatment, subsequent Bayesian adaptive control, and frequent patient evaluation. Cost-effectiveness was calculated based on real costs. The ATM group comprised 105 patients and 127 patients with nonguided TDM who were followed up as controls. Forty-eight of the ATM and 62 of the nonguided TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(169 citation statements)
references
References 25 publications
3
159
0
7
Order By: Relevance
“…23 Aminoglycoside dosing is optimized via the administration of large (once daily) doses up to 7 mg/kg for gentamicin and tobramycin and up to 20 mg/kg for amikacin, aiming at a serum peak/MIC ratio of 8-12 (individual MIC or local data), which also minimizes nephrotoxicity. 28 Active therapeutic drug monitoring 29 should be performed to avoid toxic drug levels arising via accumulation. Optimization of vancomycin dosing is achieved by using a loading dose (up to 35 mg/kg) and ensuring optimal trough levels of approximately 15 mg/L, either by twice-daily administration or continuous infusion, in order to achieve an (AUC) 0-24 : MIC ratio of more than 400, which correlates with positive outcomes in patients with MRSA bacteremia.…”
Section: This Issue Of Haematologica 21mentioning
confidence: 99%
“…23 Aminoglycoside dosing is optimized via the administration of large (once daily) doses up to 7 mg/kg for gentamicin and tobramycin and up to 20 mg/kg for amikacin, aiming at a serum peak/MIC ratio of 8-12 (individual MIC or local data), which also minimizes nephrotoxicity. 28 Active therapeutic drug monitoring 29 should be performed to avoid toxic drug levels arising via accumulation. Optimization of vancomycin dosing is achieved by using a loading dose (up to 35 mg/kg) and ensuring optimal trough levels of approximately 15 mg/L, either by twice-daily administration or continuous infusion, in order to achieve an (AUC) 0-24 : MIC ratio of more than 400, which correlates with positive outcomes in patients with MRSA bacteremia.…”
Section: This Issue Of Haematologica 21mentioning
confidence: 99%
“…PK/PD modelling suggests that a daily 10 mg/kg dose of gentamicin or tobramycin provides an 80% probability of response, even for an MIC of 4.0 mg/mL, with a negligible likelihood of toxicity [16]. As stated before, the dosage regimen for the individual patient needs to ensure an adequate drug exposure in this patient in relation to the MIC and should be re-evaluated according to TDM [17].…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…Ideally, a process of therapeutic drug management is adopted that combines the measurement of drug levels with the application of pharmacokinetic and pharmacodynamic principles. A few prospective studies using population models and Bayesian feedback have shown the superiority of model-based PK/PD guidance, both in terms of cost effectiveness and better clinical outcomes including better survival (van Lent-Evers et al 1999;Leon-Djian et al 2011).…”
Section: Pk/pd Model-based Antimicrobial Therapymentioning
confidence: 99%